The level of awareness of elements of national heritage among intermediate school students in the city of Abha - Masmali, Ali Essa Hadi; Alwadai, Mesfer Ahmad Mesfer (Journal of Curriculum and Teaching Methodology, 2024)
The study aimed to assess the level of awareness of national heritage elements among intermediate school students in Abha city, Saudi Arabia. The study adopted a descriptive approach and included a sample of 378 students from schools in Abha city, selected randomly. The researcher utilized a questionnaire as a data collection tool, consisting of 24 items. The data were collected, analyzed, and the results indicated that the level of awareness of national heritage elements among middle school students in Abha city was moderate. Students showed higher awareness levels regarding customs and traditions, as well as folk arts and literature. However, the results revealed a lower level of awareness among students regarding traditional crafts and industries. The study recommended the activation of national occasions such as National Day, Founding Day, Saudi Flag Day, and national festivals to enhance students' awareness of national heritage in public education. It also emphasized the importance of community participation between the Ministry of Education and relevant heritage authorities, such as organizing school visits to museums and festivals to connect students with their national heritage.
Keywords: Awareness level; national heritage elements; middle school students